Airliner conceptual designs for the application of alternative fuels - Chan, Joseph; Sun, Yicheng; Smith, Howard (American Institute of Aeronautics and Astronautics (AIAA), 2023)
This paper investigates the application of alternative fuels in conventional tube-and-wing aircraft configuration. Potential alternative fuel choices include biofuel, liquid hydrogen, liquefied natural gas, ammonia and methanol. A comprehensive mission range starting from 2000 nautical miles to 8500 nautical miles is explored, designed and analysed using GENUS, an in-house built multidisciplinary design analysis and optimization platform. It is expected to see a progressive change for each fuel type and capacity combination over different mission ranges. The gradient of these trends should be different which potentially demonstrates the additional benefits of using alternative fuels. The aim of this study is 1) to determine how different fuel properties will affect the designs and performance of aircraft, 2) to quantify the reduction of GHG emission by utilising alternative fuel. The results show cryogenic fuel, which required fuselage fuel tanks and external fuel tanks, will noticeably increase energy consumption due to drag and weight penalties. Meanwhile, the use of hydrogen and biofuel can significantly reduce life cycle GHG emissions if only the fuel is produced in sustainable pathways.